Building upon the success of CART19: chimeric antigen receptor T cells for hematologic malignancies. Issue 9 (2nd September 2018) - Rotolo, Antonia; Karadimitris, Anastasios; Ruella, Marco
Abstract: Chimeric antigen receptor T cell (CART) therapy has dramatically changed the therapeutic prospects for B cell malignancies. Over the last decade CD19-redirected CART have demonstrated the ability to induce deep, long-lasting remissions and possibly cure patients with relapsing B cell neoplasms. Such impressive results with CART19 fostered efforts to expand this technology to other incurable malignancies that naturally do not express CD19, such as acute myeloid leukemia (AML), Hodgkin lymphoma (HL) and multiple myeloma (MM). However, to reach this goal, several hurdles have to be overcome, in particular: (i) the apparent lack of suitable targets as effective as CD19; (ii) the immunosuppressive tumor microenvironment; (iii) intra-tumoral heterogeneity and antigen-negative relapses. Therefore, new strategies that allow safer and more potent CART platforms are under development and may provide grounds for new exciting breakthroughs in the field.